The use of Big Data and Artificial Intelligence: to prevent and detect fraud - Ramos, José Ricardo Marcondes (2021)
The development and increased adoption of different IT trends is fostering the evolution and application of Big Data and Artificial In- telligence in many contexts of society and different business sectors. The financial services are the leading field in investment in advanced technology for continuous monitoring, transaction analysis, anomaly detection, data review, pattern recognition and other emerging tech- niques. In this article, we are going to analyse the role played by Big Data and artificial intelligence for fraud detection, analysing algori- thms applied to prevent and detect payment frauds and the use of these techniques in the context of corporate fraud and investigations against financial statement frauds.